Trajectories of COVID-19 vaccine intentions among U.S. adults: The role of race and ethnicity - Michael D. Niño; Brittany N. Hearne; Tianji Cai (Elsevier, 2021)
Research examining whether intentions to get a COVID-19 vaccine change over time is scarce. Moreover, the deep and pervasive history of medical racism in the U.S. has created a context in which some racial and ethnic groups exhibit greater levels of COVID-19 vaccine hesitancy; yet few researchers have attempted to determine whether these patterns persist with time. The purpose of this study was twofold: (a.) assess the role of time in COVID-19 vaccine intentions from April 2020 to January 2021, and (b.) examine whether race and ethnicity shape COVID-19 vaccine intention trajectories. Data were drawn from 9 waves of the Understanding America Study (n = 5023), a national probability panel study of U.S. adults. Multilevel logistic regression models were used to assess overall COVID-19 vaccine intention trajectories and trajectories by race and ethnicity. Results demonstrate intentions to get a COVID-19 vaccine significantly decreased from April 2020 to November 2020, but by January 2021, intentions to get a COVID-19 vaccine slightly increased. Findings also show trajectories significantly differed by racial and ethnic background. Asian/Pacific Islanders had the highest probability of likely getting a COVID-19 vaccine at baseline, followed by Whites and Latina/os. Black Americans exhibited the lowest probability of likely getting vaccinated, and, in most cases, the gap between Black Americans and other racial groups grew over time. Key findings from this study demonstrate that, among U.S. adults, time and race and ethnicity play significant roles in COVID-19 vaccine intentions. Understanding the role of time and race and racism in shaping COVID-19 vaccine intention trajectories can help government agencies and public health experts tasked with administrating vaccines better understand disparities in vaccine uptake. Highlights: • Intentions to receive a COVID-19 vaccine decreased from April to November 2020. • Vaccine intentions increased slightly from November 2020 to January 2021. • Asian/Pacific Islanders had the highest probability of likely getting a COVID-19 vaccine at baseline. • Black Americans exhibited the lowest probability of likely getting vaccinated. • In most cases, the gap between Black Americans and other racial groups grew over time.